Tribological performance of hybrid polymer based composites - Hoe, Joyce Huang Jiao (2016)
Tribology involves the sliding of two surfaces and in the process, friction is produced. Overtime, these surfaces wear out and eventually lead to failure. Hence, effective lubrication is of great interest considering its wide spectrum of applications in the modern world. A study on the tribological performance of several hybrid polymeric composites was presented. The composites studied include epoxy resin containing encapsulated wax, epoxy resin containing encapsulated isocyanate and epoxy resin containing graphite. The investigated parameters comprise of the sliding duration, sliding speed, normal load and composition. Their tribological performance were analysed and compared with that of pure epoxy. The addition of encapsulated liquid wax and encapsulated isocyanate demonstrated remarkable decrease of friction coefficient with final value of 0.028 and 0.09 respectively when slid under a normal load of 10 N and sliding speed of 50 rpm for 10,000 s, compared to 0.54 in pure epoxy. Upon rupturing of the microcapsules during sliding, effective lubrication by the liquid wax and liquid isocyanate on its respective surfaces reduces friction and hence, slows down its wear rate. Furthermore, the self-healing polymer can form polyurea layers in the presence of moisture from the air, promoting wear on this artificial layer instead of its composite surface. As such, this is a significant improvement for tribological applications involving polymer based composites. Subsequently, the compressive stress was investigated. Higher compressive strength allows larger loads to be taken when applied. The self-healing polymer encapsulated in metal shell demonstrated higher compressive strength over that encapsulated in organic shell. It has a compressive stress strength of 98.25 MPa compared to 73 MPa of microcapsules with organic shell at 10 wt% of microcapsule content. As such, such a hybrid polymer based composite is expected to further enhance its tribological performance. In future, the study on the tribological performance of encapsulated isocyanate in metal shell epoxy can be conducted.